Management of primary T1–T4 glottic squamous cell carcinoma by transoral laser microsurgery. (31st August 2016) - Day, Andrew T.; Sinha, Parul; Nussenbaum, Brian; Kallogjeri, Dorina; Haughey, Bruce H.
Abstract : Objectives/Hypothesis: Evaluate the oncologic outcomes of patients with early and select advanced primary glottic squamous cell carcinoma (SCCa) managed by transoral laser microsurgery (TLM). Study Design: Retrospective cohort study. Methods: Ninety cases of TLM‐managed primary glottic SCCa were identified retrospectively using a prospectively collected database. Results: Outcomes of patients with pTis–pT2a disease (n = 65) and pT2b–pT4a disease (n = 25) were, respectively: 5‐year local control, 86.2% and 67.5%; 5‐year disease‐free survival, 64.9% and 44.9%; 5‐year disease‐specific survival, 96.4% and 59.0%; laryngeal preservation, 96.9% and 80%. Five of nine patients (56%) with supraglottic–glottic–subglottic tumors were local recurrence‐free compared to the 70 of 81 (86%) patients with glottic, supraglottic–glottic, and glottic–subglottic tumors. Seven of 13 patients (54%) with positive or indeterminate margins were local recurrence‐free compared to 68 of 77 (88%) patients with negative margins. Conclusions: Given sample size considerations, this study highlights the satisfactory oncologic outcomes of TLM‐treated glottic cancer and the potential importance of margin management and disease extension within the larynx. Level of Evidence: 4 Laryngoscope, 127:597–604, 2017